The Determinants of Individual Attitudes towards Immigrants in South Korea - Moamen Gouda; Jingyeong Song (CESifo GmbH, 2024)
This study empirically explores the economic, political and cultural, and socio-demographic determinants of Koreans' attitudes toward immigrants. Employing waves 6 and 7 of World Values Survey (WVS), our descriptive statistics show that Koreans, on average, are becoming more acceptable to foreigners living in Korea. Our results show that economic determinants, as well as educational attainment, were consistently playing a significant role in shaping Koreans' perception of immigrants. Socio-demographic factors and only a few political variables were significant in the period 2017-2020. We discuss this result and argue that, despite the looming demographic crisis, Koreans' attitude towards immigration is based on economic underpinnings rather than on political ones.
Keywords: F22; J15; J61; 330; immigration; South Korea; World Values Survey; attitudes